PROFILE OF MODERATE ATTITUDES OF UNIVERSITY STUDENTS IN EAST PRIANGAN - Hilda Ainissyifa; Irfan Nabhani, Yufi Mohammad Nasrullah, Nurul Fatonah, Fiqra Muhamad Nazib (International Journal of Teaching and Learning, 2024)
This study explores the profile of religious moderation among university students in East Priangan, Indonesia, through a quantitative survey approach. The research method involved university students as respondents who were randomly selected using stratification techniques with a total of 463 people, covering various study programs and semester levels. A structured questionnaire was used to collect data on views on controversial issues, such as Pancasila- religion relations, the caliphate state, respect for national symbols, and perceptions of violence. The analysis yielded an in-depth understanding of the dynamics of religious attitudes among university students. The results of this study provide a comprehensive picture of religious moderation at the academic level, providing a foundation for designing effective educational strategies. The implications of the findings can assist policy makers, educators, and practitioners in understanding and responding to the development of religious attitudes in academic communities.